Pengaruh Kunjungan Rumah Terhadap Tingkat Kemandirian Keluarga dan Pemenhuhan Tugas Kesehatan Keluarga - Roswita, Ria; Nurhayati, Nurhayati (Jurnal Skala Kesehatan, 2024)
Family is an important aspect in improving public health and the entry point in providing health services in the community and plays a role in improving public health. While in South Kalimantan, only 24.2% of families are considered healthy. This study aims to assess the effect of home visits by nurses on the level of independence and fulfillment of family health tasks with non-communicable diseases. The study was conducted in the Working Area of Martapura 1 Health Center and Martapura 2 Health Center, Banjar Regency. The sample of this study was 20 families with non-communicable diseases selected using purposive sampling techniques. The results of the research analysis with Wilcoxon showed that home visits had an effect on the level of family independence and fulfillment of family health tasks with a p value of 0.00 <0.05. This indicates the need to increase the implementation of home visits by nurses in increasing the level of family independence and fulfillment of family health tasks with non-communicable diseases in Indonesia.